2010
DOI: 10.3844/ajassp.2010.1195.1199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Time to the Antioxidant Activity in Plecranthus amboinicus Lour.

Abstract: Problem statement: Processing of food involving heat will contribute to loss of nutritional content, thus it is important to measure and control temperature and time to reduce the loss. Approach: Examine the effects of variations in boiling temperature and boiling time on the antioxidant activity of the boiling extract of Plecranthus amboinicus Lour. Fresh plants were boiled at 45, 60, 100 and 120°C for 1, 2 and 3 h respectively. The decoction was then filtered and the antioxidant activities of the extracted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Also, changing the ethanol concentration changes the physical properties of the solvent which significantly affected the extraction process (Chew et al, 2011). These observations were in accordance with earlier studies which reported that higher temperature, solvent concentration and acidic medium resulted in better extraction yield (Caunii et al, 2012;Rahim et al, 2010).…”
Section: Influence Of Extraction Parameters On Responses (Ty Tac Tpc Frap and Dpph)supporting
confidence: 93%
“…Also, changing the ethanol concentration changes the physical properties of the solvent which significantly affected the extraction process (Chew et al, 2011). These observations were in accordance with earlier studies which reported that higher temperature, solvent concentration and acidic medium resulted in better extraction yield (Caunii et al, 2012;Rahim et al, 2010).…”
Section: Influence Of Extraction Parameters On Responses (Ty Tac Tpc Frap and Dpph)supporting
confidence: 93%
“…As reported previously elsewhere that in Bataknese traditional cuisine, Torbangun is used for the induction of lactation soon after giving birth [22][23][24][25]. The use at the time of birth might have clinical importance due to its observed contents of phytochemicals and antioxidants [26]. The results on the microbial activity in relation to the treatment with extracts are shown in the Tables 3-5.…”
Section: Resultsmentioning
confidence: 89%
“…Antioxidants are important compounds that can be produced by living organisms, as can be obtained from many natural sources, and protect their health by damping active oxygen and free radicals (Phachonpai, Wattanathorn, Muchimapura, Tong‐Un, & Preechagoon, ; Rahim, Salihon, Yusoff, Bakar, & Damanik, ; Tong‐Un, Muchimapura, Phachonpai, & Wattanathorn, ). Temperature is one of the most important factors affecting antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%